Microbiological environment of endoscopic laboratory and the safety of the patient - Muczyn, Aneta; Zielińska, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2007)
There is a dynamic development of endoscopic diagnostics seen in the last decades. It not only gives the patient a chance of early diagnosis and introducing the proper treatment but it also brings a dangers resulting from improperly decontaminated endoscopic equipment. There are several microorganisms transmitted via endoscopic equipment such as: Gram (+) and Gram (-) bacteria, viruses, fungus. Although we do not know everything about causes, ways of spreading and prevention of nosocomial infection, infections transmitted via endoscopic equipment must be prevented by all available methods. Methods of prevention of nosocomial infections are: mechanical cleaning, disinfection of endoscopes, sterilization of endoscopic accessories, best clinical practice, strict aseptic and antiseptic techniques and medical training. The aim of the paper is to overview the microbiological environment of endoscopic laboratory and its influence on patient safety and quality of services.